2019
DOI: 10.31173/bomj.bomj_164_16
|View full text |Cite
|
Sign up to set email alerts
|

Nasal Carriage of Methicillin Resistant Staphylococcus aureus among Healthcare Workers in University of Maiduguri Teaching Hospital

Abstract: Background: Knowledge of prevention and removing the barriers of stigma and discrimination is a critical public health issue for HIV/AIDS prevention strategies in Nigeria. Objective: This paper is aimed at accessing the knowledge of HIV/AIDS prevention, causes and effects of stigma and discrimination towards people living with HIV/AIDS (PLWHA), among the final year dental students. Methodology: This was a descriptive cross-sectional study among final year dental students in accredited dental schools in Nigeria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…The total prevalence of MRSA in this study was 11.2% (95% CI: 7.8%, 15.4%). This coincides with results reported from studies carried out in Nigeria (13.5%) 22 and India (12%), 20 Ethiopia (12.7%). 12 However, our result was higher than the study reported from Nepal (3.4%), 18 Ethiopia (5.7%), 23 and Odisha (7.5%).…”
Section: Discussionsupporting
confidence: 92%
“…The total prevalence of MRSA in this study was 11.2% (95% CI: 7.8%, 15.4%). This coincides with results reported from studies carried out in Nigeria (13.5%) 22 and India (12%), 20 Ethiopia (12.7%). 12 However, our result was higher than the study reported from Nepal (3.4%), 18 Ethiopia (5.7%), 23 and Odisha (7.5%).…”
Section: Discussionsupporting
confidence: 92%